Performance of mortality rates using deep learning approach / Mohamad Hasif Azim and Saiful Izzuan Hussain - Azim, Mohamad Hasif; Hussain, Saiful Izzuan (2021)
Mortality has a vital role in population dynamics and is critical in a wide variety of fields, including demography, economics, and social sciences. This study aims to model and compare the mortality rate using two different models; the Lee-Carter model and Deep Neural Network (DNN). The sample data used is the case of the United Kingdom population. Mortality rates were modeled with the Lee-Carter model and deviance goodness of fit were used to test the model's suitability of the data. Next, mortality rates are modeled with the Deep Neural Network (DNN) and both models are compared based on the mean square error (MSE) values. The results showed that the DNN model fits the best. Overall, we conclude that DNN approach appears to be a potential model to model and forecast population mortality.